Classification and Dynamics of Class of Î¾(as)-QSO - Qaralleh, Izzat; Ab Ghani, Ahmad Termimi; Hamza Abd El-Qader, Hamza Abd (Journal of Mathematical and Fundamental Sciences, 2020)
The current study provides a new class of Î¾(as)-QSO defined on 2D simplex and classifies it into 18 non-conjugate (isomorphic) classes. This classification is based on their conjugacy and the remuneration of coordinates. The current study also examines the limiting points associated with the behavior of trajectories for four classes defined on 2D simplex.